The Influence of Psychocybernatic Integration and Entrepreneurial Training On The Motivation of Entrepreneurship - Marganingsih, Anna; Dewiwati Pelipa, Emilia (Devotion : Journal of Research and Community Service, 2023)
Indonesia is a country with the fourth most populous population in the world, with a large population causing a depletion of jobs. Furthermore, with fewer jobs, many people become unemployed. One way to reduce unemployment is by entrepreneurship. However, without motivation, entrepreneurship will not work. Thus, this study aims to determine the effect of psychocybernatic integration and entrepreneurial training on the entrepreneurial motivation of students of the Economics Education Study Program STKIP Persada Khatulistiwa Sintang. The research was conducted using a descriptive method with a quantitative approach. The results of the research conducted show that the effect of psychocybernatic integration (X1) on entrepreneurial motivation (Y) has a significance value of 0.154. So that means psychocybernatic integration has a negative effect on entrepreneurial motivation. Then, the effect of entrepreneurship training on entrepreneurship motivation has a significance value of 0.003. So that means entrepreneurship training has a positive and significant effect on entrepreneurial motivation